The influence of scan duration on pulmonary capillary hemorrhage induced by diagnostic ultrasound - Miller, Douglas L. (Ultrasound Med Biol, 2016)
Diagnostic ultrasound can induce pulmonary capillary hemorrhage (PCH) in rats and display this as “comet-tail” artifacts (CTA) after a time delay. To test the hypothesis that no PCH occurs for brief scans, anesthetized rats were scanned using a 6 MHz linear array for different durations. PCH was characterized by ultrasound CTAs, micro-computed tomography (µCT) and measurements of fixed lung tissue. The µCT images showed regions of PCH, sometimes penetrating the entire depth of a lobe, which were reflected in the fixed tissue measurements. At −3 dB power, PCH was substantial for 300 s scans but not significant for 25 s scans. At 0 dB, PCH was not strongly dependent on scan durations of 300 s to 10 s. Contrary to the hypothesis, CTAs were not evident during most 10 s scans (p>0.05), but PCH was significant (p=0.02), indicating that PCH could occur without evidence of the injury in the images.